Análise experimental e modelagem do atrito em escoamento turbulento totalmente desenvolvido de fluido não-Newtoniano em tubulações de superfície lisa e rugosa - Santos, Cecilia Mageski Madeira (2018)
Flow of newtonian fluids over smooth and rough surfaces have been a topic of great academic interest for many decades. With the advancement of oil and gas exploration the transport of non-newtonian fluids, has generated much research, and little is known about the flow over rough surfaces due to the complexity and difficulty of generating experimental data. In the literature there are papers that present the friction factor equation for the non-newtonian fluid for smooth surfaces (DODGE e METZNER, 1959; SHAVER e MERRILL, 1959; SZILAS et al., 1981), and for rough surface (SHUKRI, 2016; SZILAS et al., 1981). On all of those papers, the influence of the fluid rheology on the rough component of the friction equation is neglected. An experimental apparatus, including six stainless steel pipe circuits with different roughness, was tested and validated with newtonian fluid (water), and the non-newtonian working fluid for each test was prepared, and an extensive measurement campaigns conducted. Measurements of pressure drop and flow rate, using newtonian fluid for validation of the apparatus and non-newtonian fluid (CMC - Carboxymethylcellulose) were made, aiming to identify the behavior of the flow in this types of surfaces. The rheological characteristics of the fluid were made by rotational rheometer testing throughout the experimental run. The final objective of this thesis is to analyze the influence of the change of the surface roughness in the flow of newtonian and non-newtonian fluid.